Aerosol filtration efficiency of household materials for homemade face masks: Influence of material properties, particle size, particle electrical charge, face velocity, and leaks. Issue 1 (2nd January 2021) - Drewnick, Frank; Pikmann, Julia; Fachinger, Friederike; Moormann, Lasse; Sprang, Fiona; Borrmann, Stephan
Abstract: As a consequence of the COVID-19 pandemic caused by the SARS-CoV-2 virus, the widespread daily use of face masks is promoted worldwide. Particle-size dependent filtration efficiencies ( FE ; dp  =  30 nm–10 µm), applying a particle counting approach, and additionally pressure drops (Δ p ) were determined for 44 samples of household materials and several medical masks. Huge FE differences were found between sample materials and for different particle sizes, spanning from <10% up to almost 100%. Minimum FE were determined for dp = 50–500 nm particles with significantly larger values for dp  = 30 nm particles and especially for those with dp > 2.5 µm. Measurements at different numbers of layers showed that stacks of textiles can be treated as separate filters and total FE and Δ p can readily be estimated from the features of the individual layers, leaving laborious measurements of individual combinations obsolete. For many materials, electrostatic attraction contributes strongly to overall FE for particles up to 100 nm diameter. Measurements with defined leaks showed that already a small fractional leak area of 1–2% can strongly deteriorate total FE . This is especially the case for particles smaller than 5 µm diameter, where FE dropped by 50% or even two thirds. Our measurements show that by stacking an adequate number of layers of many fabrics, decent filtration efficiencies can be reached for homemade face masks over large particle size ranges with acceptable pressure drop across the material. Very important, however, is good fit of the masks to minimize leak flows and selection of non-hazardous mask material.